Wybrane regulacje Kodeksu spółek handlowych w świetle konstytucyjnego modelu ochrony własności - Ochmann, Paweł (Wydawnictwo Naukowe UAM, 2019)
The article confronts specific solutions adopted in the Code of Commercial Companies and Partnerships with the patterns of the constitutional control of law resulting from the Constitution of the Republic of Poland in the form of the right of ownership. Its aim is to answer the question whether the constitutionality of commercial law institutions should be assessed autonomously, taking into account the specificity of commercial companies law. The author puts forward a thesis that just as there is a principle of autonomy of commercial law within the principle of unity of civil law, within the framework of constitutional law, the regulations of law and commerce also have autonomy which influences the process of assessing the conformity of particular subjects of control with the models defined in the Constitution of the Republic of Poland. As one of the specific elements of commercial law in relation to the Constitution, the necessity of weighing the opposing interests of the same good, i.e. the right to ownership is pointed out. The paper discusses in detail the institution of forced buyout (squeeze-out) in the context of the judgment of the Constitutional Tribunal (Case No. P 25/02). The issue of legitimacy to appeal against the resolution of the General Shareholders Meeting of a company from the point of view of the right of ownership is also discussed. In the author’s opinion, the right to appeal against the resolution, which prima facie at the constitutional law level could be associated with the constitutional right to a court, takes the form of a corporate right of a shareholder resulting from a constitutional right of ownership, of which a share is one of the forms. Therefore, it has a derivative character. The considerations contained in the text lead to the recognition of the admissibility of an autonomous interpretation of company law regulations when assessing their compliance with the Constitution. When assessing constitutionality, the legal character and specificity of the subject of control should be taken into account.
Selected regulations of the Code of Commercial Partnerships and Companies in the light of the constitutional model of the right of ownership protection
Keywords: forced buyout; squeeze-out; weighing of goods; autonomy of commercial law